Quality of life in men with chronic scrotal pain. Issue 1 (1st January 2017) - Aljumaily, Aosama; Wu, Christopher; Al-Khazraji, Hind; Gordon, Allan; Lau, Susan; Jarvi, Keith A.
ABSTRACT: Background : Chronic scrotal pain (CSP) is a common and often debilitating condition found in up to 4.75% of men. There is little written on the impact of CSP on men's lives. Aim : The aim of this study was to understand the impact of CSP on men's lives. Methods : Patients with CSP were prospectively asked to complete a comprehensive questionnaire, including questions on quality of life (QoL), activities, and mood. Results : The mean age of the 131 patients was 43 years. Pain was intermittent, with severe pain episodes (mean pain scores 7.2 ± 2 out of 10) affecting men on average 40% ± 30% of the time. Overall, 88/131 (67.17%) of patients responded that they felt "unhappy" or "terrible" with their present situation. More than 40% of patients complained of depressive symptoms more than half the days of the month. Normal activities were adversely affected, with 68/131 (51.90%) reporting limited ability to work, 93/131 (70.99%) patients reporting decreased physical activity, and 81/131(61.83%) reporting decreased sexual activity. Comparing men with pain levels ≥ 7/10 vs. those with pain levels < 7/10, 47% (41/88) vs. 8.1% (3/37) reported that they felt "terrible, " 40% (35/88) vs. 13% (5/38) had depressive feelings more than half the time, and 35% (28/80) vs. 16% (6/38) felt little pleasure doing things ( P < 0.01 for all). Conclusion : Our study suggests that QoL, mood, and the ability to perform normal activities are profoundly disturbed in CSP patients and that the pain severity is directly related to QoL.